The influence of migraine and female hormones on capsaicin-induced dermal blood flow. (October 2017) - Ibrahimi, Khatera; Vermeersch, Steve; Frederiks, Pascal; Geldhof, Vincent; Draulans, Cedric; Buntinx, Linde; Lesaffre, Emmanuel; MaassenVanDenBrink, Antoinette; de Hoon, Jan
Background: Migraine is much more common in females than in males, and occurrence is associated with changes in female sex hormones. Calcitonin gene-related peptide (CGRP) plays a key role in migraine, and variations in female sex hormones may affect CGRP sensitivity and/or production. Objectives: Investigate repeatability, gender differences, influence of the menstrual cycle and of migraine on CGRP-dependent changes in dermal blood flow (DBF). Methods: CGRP-dependent increases in DBF were assessed using laser Doppler perfusion imaging after topical application of 300 or 1000 µg capsaicin on the forearm of healthy subjects and migraine patients. Results: In healthy males, DBF response did not vary over time and was comparable with DBF in male migraineurs. In healthy females, capsaicin-induced DBF responses to both doses of capsaicin were higher during menstruation compared to the late-secretory phase (p < 0.05); this menstrual cycle dependence was absent in female migraine patients. Compared to healthy subjects, female migraineurs displayed a higher DBF response both during menstruation and during the late-secretory phase (p < 0.05). Conclusions: An increased capsaicin-induced, CGRP-mediated DBF response was observed during menstruation in healthy women, but in female migraine patients this increased response was not affected by the menstrual cycle.